PENDUGAAN POTENSI AIR TANAH WILAYAH PESISIR KABUPATEN PASIR KALIMANTAN TIMUR - Indriatmoko, Robertus Haryoto (Center for Environmental Technology, 2006)
Coastal aquifers are an important ground-water resource for urban, fisheries, and agriculture areas. Coastal aquifer system at coast of Tanah Grogot Regency, at East Kalimantan Province, is important to community, but existing aquifers are not productive as ground water resources and therefore to meet community needs of water, a geoelectricity survey need to be conducted to find aquifers and this information will be used for development of water resources planning and method to be used for geoelectricity survey is rock layer resistivity. Result of this survey will identify aquifer layers as source of water.Ã‚Â Katakunci : Wilayah pesisir, geolistrik, metoda schlumberger, satu dimensi, akuifer, air tanah, kualitas air, kabupaten pasir,tanah grogot, kalimantan timur